Embodied Cognition Profile of Junior High School Students in Solving Math Problems Based On Different Learning Styles - Ma'allaili, Serlly Hindun; Budayasa, I Ketut; Susanah, Susanah (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2024)
The purpose of this study is to describe the embodied cognition profile of junior high school students in solving math problems based on different learning styles (including visual, audio, and kinesthetic learning styles). Embodied cognition is a cognitive process resulting from a person's sensorimotor activities, involving interaction with the surrounding environment to obtain and represent their knowledge, in gesture and utterance. The instruments used include a learning style questionnaire, math problem-solving tasks, interview guidelines, and observation sheets. The results of this study are: (1) students with visual learning styles bring up gestures, namely pointing, representational, and writing gestures, and bring up utterances such as clear speech and tone of voice, calm facial expressions, focused gaze and eye movements, body calmness; (2) students with audio learning styles bring up two gestures, namely pointing gestures and writing gestures, and bring up utterances such as clear speech and tone of voice sometimes soft, calm facial expressions sometimes hesitant, focused gaze and eye movements, hands moving when explaining something; (3) students with kinesthetic learning styles bring up gestures, namely pointing, writing, and representational gestures, and bring up utterances such as clear speech and tone of voice, calm facial expressions, focused gaze and eye movements, hands moving when explaining something. Keywords: embodied cognition, problem-solving, learning style